1997
DOI: 10.1111/1523-1747.ep12319282
|View full text |Cite
|
Sign up to set email alerts
|

Altered Permeability and Disordered Cutaneous Immunoregulatory Function in Mice with Acute Barrier Disruption

Abstract: In vivo and in vitro T-cell-activating ability of murine epidermal cells (EC) was investigated in acutely barrier-disrupted skin by extraction of epidermal lipids with acetone or removal of corneocytes by tape stripping. Contact sensitivity (CS) to 2,4-dinitrofluorobenzene (DNFB) and picryl chloride (PCl) and contact photosensitivity (CPS) to tetrachlorosalicylanilide (TCSA) were significantly augmented when challenged or sensitized at sites treated with acetone 24 h before, compared with the intact skin. CS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 48 publications
4
87
0
Order By: Relevance
“…28,29) After TS treatment, the RMFI values for MHC class II, CD86, CD80, and CD54 on LCs were 1.94±0.27, 1.66±0.25, 1.17±0.10, and 1.26±0.10, respectively, and the degree of expression of MHC class II and CD86 tended to be higher than those of the control group. This result was consistent with the findings of Seo et al 29) and Nishijima et al, 30) suggesting the relevance of TS treatment as a positive control. To compare the effect of insertion depth of microneedles on the skin, different needle sizes (500 or 300 µm) were used.…”
Section: Fig 5 Expression Of Mhc Class II Cd86 Cd80 and Cd54 On supporting
confidence: 93%
See 3 more Smart Citations
“…28,29) After TS treatment, the RMFI values for MHC class II, CD86, CD80, and CD54 on LCs were 1.94±0.27, 1.66±0.25, 1.17±0.10, and 1.26±0.10, respectively, and the degree of expression of MHC class II and CD86 tended to be higher than those of the control group. This result was consistent with the findings of Seo et al 29) and Nishijima et al, 30) suggesting the relevance of TS treatment as a positive control. To compare the effect of insertion depth of microneedles on the skin, different needle sizes (500 or 300 µm) were used.…”
Section: Fig 5 Expression Of Mhc Class II Cd86 Cd80 and Cd54 On supporting
confidence: 93%
“…Tokura et al demonstrated that epidermal LCs activated by TS treatment migrated to the peripheral draining lymph nodes at 24-48 h after treatment. 30) Thus, this may explain the observed decrease in MHC class II staining at 24 h in our study demonstrated after TS treatment.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…[8][9][10] TS leads to removal of the outermost horny layer of the skin, resulting in enhanced permeability and maturation and activation of LCs via inflammatory cytokines secreted from keratinocytes. 11,12 The barrier function of the SC can also be bypassed by hydration of the skin, which leads to swelling of the keratinocytes and pooling of fluid into intercellular spaces. This kind of pretreatment of the skin leads to development of humoral 13,14 and Th responses after TCI with proteins or peptides.…”
mentioning
confidence: 99%